2017
DOI: 10.1038/s41598-017-02409-5
|View full text |Cite
|
Sign up to set email alerts
|

Basin stability for chimera states

Abstract: Chimera states, namely complex spatiotemporal patterns that consist of coexisting domains of spatially coherent and incoherent dynamics, are investigated in a network of coupled identical oscillators. These intriguing spatiotemporal patterns were first reported in nonlocally coupled phase oscillators, and it was shown that such mixed type behavior occurs only for specific initial conditions in nonlocally and globally coupled networks. The influence of initial conditions on chimera states has remained a fundame… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(32 citation statements)
references
References 57 publications
0
32
0
Order By: Relevance
“…From the discovery of the chimera states, the initial conditions play a crucial role. For many coupled systems, chimera states emerge only for a few specific initial conditions [57,58]. Especially in multi-stable systems, the emergence of chimera states depends on the initial conditions.…”
Section: Global Stability Of the Chimera And Coherent Statesmentioning
confidence: 99%
See 2 more Smart Citations
“…From the discovery of the chimera states, the initial conditions play a crucial role. For many coupled systems, chimera states emerge only for a few specific initial conditions [57,58]. Especially in multi-stable systems, the emergence of chimera states depends on the initial conditions.…”
Section: Global Stability Of the Chimera And Coherent Statesmentioning
confidence: 99%
“…Especially in multi-stable systems, the emergence of chimera states depends on the initial conditions. Since the isolated Leech neuronal model itself possesses multi-stable behavior, we now investigate the robustness of the initial conditions on the chimera states using basin stability measurement [58,59]. This is a non-linear, non-local approach, that can be easily applied to high-dimensional multi-stable systems.…”
Section: Global Stability Of the Chimera And Coherent Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the concept of basin stability (BS) was suggested to describe the stability against large perturbations [15,[18][19][20]. The BS method was later used in various applications [21][22][23][24] and also confirmed experimentally [25]. BS is a probabilistic measure that characterizes the likelihood that the perturbation is 'safe', i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have also reported emergence of chimera states in multiplex networks 26 . The effect of initial conditions on chimera states recently investigated using a basin stability approach 27 . We raise one important question here: how to control chimera pattern [28][29][30][31] , mainly, how to restrict the pattern to a targeted population or to a selected set of oscillators?…”
Section: Introductionmentioning
confidence: 99%